REDESAIN WEB G SPORTS CENTER GUNUNG PANGILUN PADANG - ABK JAILANI, Drs. Syafei. M.Ag, Eliya Pebriyeni, S.Pd. M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Purpose of this final work is This thesis objectives are (1) Web Design Designing the new G Sports Center with a more interesting and more complete, (2) Designing forms of visual and verbal in Web Design G Sports Center so that the aims and objectives are achieved, (3) creating a characteristic that can be recognized easily by the customer. Sources of this thesis is the method of data collection in the form of field observations, interviews, as well as through the documentation at G Sports Center. Final work in the form of an attractive Web Design and communicative, G Sports Center Website visitors can find information about G Sports Center for the Web has provided information in the form of verbal or visual Keyword: Design,Sports,and Web